Diagnostic, training and realisation of strength condition of swimmers with use of feedback diagnostic simulator "ART" - Petriaev, A.; Kleshnev, I. (Biomechanics and Medicine in Swimming X, 2006)
This paper describes opportunities of use of the Computer diagnostic exerciser in diagnostic, training and realisation of sports-men's strength potential. The researches were held using the diagnostic exerciser "ART", allowing to simulate water conditions in "force-velocity" parameters. The provided visual feed-back allow "controlled variations" in absolute parameters of force, power, stroke rate, length and dynamical structure of stroke. Results showed the high efficacy of the use of "ART" in: (i) quantitative and qualitative analyses of sportsman's power potential, (ii) prognosis of athletes' achievements, (iii) correction of speed and power components of stroke movement of swimmers, (iv) correction of the dynamical structure of stroke, and (v) transfer of sportsman's power potential to real swimming ability using training modes, in which the stroke velocity will correspond the record velocities of athletes.